Tracing the Paleobiology of Paedotherium and Tremacyllus (Pachyrukhinae, Notoungulata), the Latest Sciuromorph South American Native Ungulates – Part II: Orbital, Auditory, and Occipito-Cervical Regions - Ercoli, Marcos Darío (2021)
The caudal cranium and occipito-cervical region, although usually overlooked, are informative about the paleobiology of fossil mammals, allowing inquiry into vision and hearing abilities, as well as head and neck postures. Particularly for Pachyrukhinae, some related features remain unexplored. In this contribution, 22 specimens of Paedotherium and Tremacyllus were analyzed in a mainly qualitative and comparative framework. Pachyrukhines are characterized by having large orbits and hearing cavities, moderate to short necks with generalized morphologies, and S-shape postures. These features allow rejecting some types of specialized digging habits, and support the preference of open or low-humidity environments. Paedotherium typicum is distinguished by the presence of laterally oriented eyes, marked vaulted cranium and predominant short extensor and stabilizing neck muscles, and cervico-occipital-hyoid configurations suitable for ventro-flexed resting posture. These features indicate accentuated frontation and panoramic-vision, upward head postures enhancing substrate perception, and the resistance of impacts during leaping-cursorial locomotion. Conversely, P. bonaerense, and to lesser degree Tremacyllus spp., show less frontation and probably adopted more horizontal head postures. More particularly, stronger ventral and lateral neck and head flexors and extrinsic arm musculature are reconstructed for P. bonaerense, compatible with generalist or scratch-digging habits. Its smaller auditory cavities and stronger ear musculature, compared to the contemporary P. typicum and especially Tremacyllus spp., would indicate larger ears and microhabitat segregation. The integrative analysis proposed here and in the accompanying contribution aims to shed light on convergences with extant models, paleobiology, niche partitioning, and external appearance of the latest rodent-like ungulates.